(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2020)
This essay aims to give some light on how social movements are important organizations that have formed in the history of humanity to seek alternatives and solutions to living conditions that make a society more cultured, thrives and where the exercise of enjoyment Full of Human Rights since inclusion, equality and equity must be the work engine of all states. This essay also aims to give a general idea of how social movements have been doing their work in the last 5 years in Central America; As well as some challenges and challenges that exist as social movements in the region.